Financial Incentives and Gaming in Alcohol Treatment - Mingshan Lu; Ching-To Albert Ma (SAGE Publishing, 2006)
This study looks at the effect of performance-based contracting (PBC) on administrative information misreports in substance abuse treatment in Maine. For about 700 alcohol abuse treatment episodes in the period 1990-1995, we constructed clinician report gaming indicators from two data sets: the Maine Addiction Treatment System (MATS) and medical record abstracts. Gaming, in this study, refers to differences in MATS reports and the medical records for an episode. Under PBC, which was implemented in 1992, a provider's financial reward was positively related to treatment outcomes measured by some reports from MATS. We found that the introduction of PBC increased gaming. The data supported the hypotheses that clinicians overstated patient severity at the beginning of treatment episodes, and understated severity at the end.